2019
DOI: 10.1007/s10071-019-01287-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early and later life environmental enrichment and personality on attention bias in pigs (Sus scrofa domesticus)

Abstract: We investigated effects of early and later life housing on attention bias, as an indicator of affective state, in pigs differing in coping style [reactive (LR) vs. proactive (HR)]. Pigs (n = 128) in barren or enriched housing from birth (B1 vs. E1) that experienced either a switch in housing at 7 weeks of age or not (creating B1B2, B1E2, E1E2, and E1B2 treatments), were studied in a 180-s attention bias test at 11 weeks. Pigs exposed to a 10-s-auditory-and-sudden-motion threat in the test arena paid more atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 69 publications
(122 reference statements)
1
58
3
Order By: Relevance
“…Rather, the successive negative contrast test suggested a "protective" effect of early life enrichment irrespective of the current environment, as pigs reared in enriched pens were less susceptible to reward loss (46). In the attention bias test, no early life effects were found, whereas the impact of current housing was opposite to expectations, which might be due to the test circumstances (42), and found only for pigs with a proactive coping style. Thus, further research is needed to evaluate whether a change from enriched to barren housing conditions and vice versa not only affects pigs' behavior, but also their affective state in the long run.…”
Section: After the Housing Switchmentioning
confidence: 85%
See 3 more Smart Citations
“…Rather, the successive negative contrast test suggested a "protective" effect of early life enrichment irrespective of the current environment, as pigs reared in enriched pens were less susceptible to reward loss (46). In the attention bias test, no early life effects were found, whereas the impact of current housing was opposite to expectations, which might be due to the test circumstances (42), and found only for pigs with a proactive coping style. Thus, further research is needed to evaluate whether a change from enriched to barren housing conditions and vice versa not only affects pigs' behavior, but also their affective state in the long run.…”
Section: After the Housing Switchmentioning
confidence: 85%
“…On the other hand, reactive pigs may be more influenced by their long-term housing environment. Several studies reported that reactive pigs were more affected by the absence or presence of enrichment than proactive pigs (37,40,41), although we recently found that the behavior of proactive pigs in an attention bias test was more influenced by enrichment (42). Thus, the impact of enrichment and a loss or gain of enrichment may depend on the personality characteristics of the pig under study, which may therefore be relevant to take into account.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…These different personalities are expressed by consistent behavioral responses under various conditions, that can vary with different variables e.g. population density, stress and enrichment [2,3,4]. The personality of an animal can influence its welfare, as these responses can vary between individuals, i.e.…”
Section: Introductionmentioning
confidence: 99%